The Efficiency of Private E-Money-Like Systems: The U.S. Experience with National Bank Notes - Warren E. Weber (Bank of Canada, 2015)
Beginning in 1864, in the United States notes of national banks were the predominant medium of exchange. Each national bank issued its own notes. E-money shares many of the characteristics of these bank notes. This paper describes some lessons relevant to emoney from the U.S. experience with national bank notes. It examines historical evidence on how well the bank notes - a privately-issued currency system with multiple issuers - functioned with respect to ease of transacting, counterfeiting, safety, overissuance and par exchange (a uniform currency). It finds that bank notes made transacting easier and were not subject to overissuance. National bank notes were perfectly safe because they were insured by the federal government. Further, national bank notes were a uniform currency. Notes of different banks traded at par with each other and with greenbacks. This paper describes the mechanism that was put in place to achieve uniformity. The U.S. experience with national bank notes suggests that a privately-issued e-money system can operate efficiently but will require government intervention, regulation, and supervision to minimize counterfeiting, promote safety and provide the mechanism necessary for different media of exchange to exchange at par with each other.
Keywords: E41; E42; E58; 330; Bank notes; E-money; Financial services